KONFLIK KELAS DAN FENOMENA KOMUNISME DALAM HUBUNGAN STRUKTURAL MENURUT PANDANGAN KARL MARX - Ahmad Syadzali (Pascasarjana UIN ANTASARI Banjarmasin, 2014)
Classconsciousnessis the important key wordin understanding Marx's thought. This phenomenonis actually theantithesisof theHegelianway ofthinkingthat is tooidealistic, which is thenreversedbyMarxin the context ofa moreempirical view. Hence theconcept ofcommunism is evolved by laterMarx's thought interpreters which become the extreme thinking against variousideologies, including religiousideology whichis in favor of thebourgeoisie.